PENGEMBANGAN USAHA PENGOLAHAN SIWALAN (Borassus flabellifer) MENJADI SIRUP DAN NATA DI KUBU KARANGASEM - Rina Pratiwi Pudja I. A; I M. Nada; I M. A.S. Wijaya; I. A. G. Bintang Madrini; N. N. Puspawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2011)
One of agricultural commodities produced at Sukadana Village is called siwalan. In order to maintain siwalan quality after being harvested, it is required an exact preparation-method. Preparation method which is not exact will cause the siwalan quickly rotten or become infected, therefore it cannot be used as cooking spices or raw industry material. Usually, the farmers sell the siwalan directly after harvesting, so in the siwalan season, the price is very low and the farmers suffer from great loss. Sukadana village peoples have not yet had knowledge about the exact after harvesting preparation method to maintain siwalan quality with the supporting equipment. Community service activity was carried out to develop the processing siwalan to be siwalan syrup and nata at Sukadana village, Kubu sub district, Karangasem on Friday, 08 October 2010. It was attended by 37 peoples with two ways discussion method therefore they are very active asking and responding the topic. The activity like this was very useful for the people in the village. So, the same activity needs to be conducted at the other villages having the same agricultural commodity.